Sulfide solid electrolyte and preparation method and application thereof
By introducing +3 or+5 elements and O elements in sulfide solid-state electrolytes, the P-O and M-S bonds are formed, and the problem of low energy density of traditional lithium batteries and poor stability of solid electrolytes are solved, and high energy density, long cycle Improve life and safety performance.
Patent Information
- Application Number
- CN202411504947.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-11
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional liquid lithium batteries have problems with low volume energy density and weight energy density, and solid electrolytes have problems with poor chemical stability and incompatible with electrode materials.
A sulfide solid-state electrolyte is proposed, whose molecular formula is LiaP1-bMbScOdXe. By introducing M elements and O elements with +3 or +5 valence, P-O and M-S bonds are formed to enhance air stability and chemical stability, and through ball milling and calcination Process preparation.
It improves the conductivity of the sulfide solid electrolyte and its compatibility with active materials, simplifies the packaging process of bipolar batteries, and improves the energy density, cycle number and safety performance of the battery.
Smart Images

Figure BDA0005103678620000141
Abstract
Description
[0001] This application claims priority to a Chinese patent application filed on October 11, 2024, with application number 202411418926.2 and invention name “A sulfide solid electrolyte, its preparation method and application”, the entire contents of which are incorporated by reference into this application. Technical Field
[0002] The present invention relates to the technical field of lithium ion batteries, and in particular to a sulfide solid electrolyte and a preparation method and application thereof. Background Art
[0003] As an important energy storage device, lithium-ion batteries have been widely used in electric vehicles and electronic products. The current collectors of traditional liquid lithium batteries are composed of the same electrode materials on both sides, all electrodes are immersed in the same electrolyte, and each electrode is connected in parallel using external connecting wires, so a large amount of inactive materials are integrated into the battery system. This results in a significant loss of both the volume energy density and the weight energy density of lithium-ion batteries.
[0004] By introducing bipolar batteries, no electrical connectors or other accessories are used, so the battery structure and shape are simple, which can significantly improve the volume and weight energy density. However, the flow of liquid electrolyte in bipolar batteries will cause liquid short circuits in the battery, so a complex packaging process is required, which will also use a large amount of packaging materials and will also lose the energy density of the battery. Solid electrolytes can solve the problems of liquid batteries due to their solid-state properties, but solid electrolytes have problems such as poor chemical stability and incompatibility with electrode materials. Summary of the invention
[0005] The present invention proposes a sulfide solid electrolyte and a preparation method and application thereof. The sulfide solid electrolyte and a preparation method and application thereof provided by the present invention can enhance the air stability and chemical stability of the sulfide solid electrolyte, improve the electrical conductivity of the sulfide solid electrolyte, enhance the air stability, and improve the electrolyte / active material interface properties, thereby improving the compatibility with active materials, reducing the packaging steps and the use of packaging materials, and greatly improving the battery capacity, cycle number and energy density of the bipolar battery.
[0006] To solve the above technical problems, the present invention is implemented through the following technical solutions.
[0007] The present invention provides a sulfide solid electrolyte, wherein the molecular formula of the sulfide solid electrolyte is Li a P 1- b M b S c O d X e; wherein: 5 < a < 6; 0 < b < 1; 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb; X is selected from one or more of Cl, Br or I.
[0008] In one embodiment of the present invention, M is selected from one or more of Sb, In or Bi.
[0009] In one embodiment of the present invention, X is selected from Cl; the value range of b is 0 < b < 0.1.
[0010] The present invention also provides a preparation method of the above-mentioned sulfide solid electrolyte, including the steps:
[0011] According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to stoichiometry and then placed in a ball mill jar for ball milling to obtain a sulfide solid electrolyte precursor powder; and
[0012] The sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain the sulfide solid electrolyte.
[0013] In one embodiment of the present invention, the raw materials include Li 2 S, LiX, P 2 S 5 and the oxide corresponding to the M element, X is selected from one or more of Cl, Br or I, and M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb.
[0014] In one embodiment of the present invention, the ball milling time is 20h to 30h, the ball milling speed is 500rpm to 600rpm, and the ball-to-material ratio is 35:1 to 45:1.
[0015] In one embodiment of the present invention, the preset temperature is 450°C to 550°C, and the calcination time is 20h to 30h.
[0016] The present invention also provides a all-solid-state lithium-ion battery, at least including:
[0017] A plurality of bipolar electrodes, with a positive electrode active material layer and a negative electrode active material layer respectively arranged on both sides of the bipolar electrode, and the positive electrode active material layer and the negative electrode active material layer between adjacent bipolar electrodes are arranged oppositely; and
[0018] A solid electrolyte membrane, which is arranged between adjacent bipolar electrodes;
[0019] Wherein, the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte membrane include the above-mentioned sulfide solid electrolyte.
[0020] In one embodiment of the present invention, in the positive electrode active material layer or the negative electrode active material layer, the content of the sulfide solid electrolyte is 20 wt % to 30 wt %.
[0021] In one embodiment of the present invention, the solid electrolyte membrane includes the sulfide solid electrolyte and a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.
[0022] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.
[0023] In summary, the present invention proposes a sulfide solid electrolyte and a preparation method and application thereof, which can enhance the intrinsic resistance of the sulfide solid electrolyte to atmospheric degradation and effectively reduce H 2 The generation of S increases the possibility of the battery in actual production, thereby enhancing the air stability and chemical stability of the sulfide solid electrolyte. The sulfide solid electrolyte has higher stability and specific reactivity, which can improve the conductivity of the sulfide solid electrolyte, enhance air stability, and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials. The sulfide solid electrolyte matrix structure can be stabilized to improve ionic conductivity and electrochemical stability, and improve voltage stability. By using solid electrolyte membranes in bipolar batteries, the packaging steps can be reduced, the packaging process of bipolar batteries can be simplified, and the use of packaging materials can be greatly reduced. The battery capacity, number of cycles and energy density of the bipolar battery can be greatly improved, while the safety performance of lithium ions can be improved. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0026] The technical solutions of the present invention will be further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0027] The present invention provides a sulfide solid electrolyte, and the molecular formula of the sulfide solid electrolyte is Li a P 1- b M b S c O d X e , where 5 < a < 6; 0 < b < 1; 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from, for example, one or more of Al, Ga, In, Ti, Sc, Sb, Bi, As, V or Nb, etc., and X is selected from, for example, one or more of Cl, Br or I. Among them, introducing +3 or +5-valent M elements and O elements into the sulfide solid electrolyte rich in halogen elements will form P-O and M-S bonds in the crystal structure, thereby increasing the intrinsic resistance to atmospheric degradation and effectively reducing the generation of H 2 S, increasing the possibility of the battery in actual production, thereby enhancing the air stability and chemical stability of the sulfide solid electrolyte.
[0028] In an embodiment of the present invention, M is selected from, for example, one or more of Sb, In or Bi. The formed Sb-S / Bi-S / In-S and other bonds have a relatively high binding energy, making the chemical bonds stronger and difficult to be damaged by external influences. Thus, the sulfide solid electrolyte has high stability and specific reactivity, can improve the conductivity of the sulfide solid electrolyte, enhance air stability, and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. X is selected from, for example, Cl. Due to the introduction of halogen elements, the matrix structure of the sulfide solid electrolyte is stabilized to improve ionic conductivity and electrochemical stability and improve voltage stability. The value range of b is 0 < b < 0.1. In an embodiment of the present invention, when M is +5-valent, b is preferably 0.04, and when M is +3-valent, b is preferably 0.02 to optimize the battery capacity, cycle number and energy density of the lithium-ion battery.
[0029] The present invention also provides a method for preparing a sulfide solid electrolyte, which at least includes the following steps:
[0030] According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to stoichiometry and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder;
[0031] The sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain the sulfide solid electrolyte.
[0032] In one embodiment of the present invention, according to the chemical formula of the sulfide solid electrolyte Li a P 1-b M b S c O d X e , the raw materials are mixed uniformly according to the stoichiometric ratio, wherein the raw materials include, for example, Li 2 S, LiX, P 2 S 5 and oxides corresponding to the M element, X is selected from one or more of Cl, Br or I, and M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, etc. After the raw materials are evenly mixed, they are placed in a ball mill, wherein the ball-to-material ratio is, for example, 35:1 to 45:1, the ball milling speed is, for example, 500 rpm to 600 rpm, and the ball milling time is, for example, 20 h to 30 h, to obtain a sulfide solid electrolyte precursor powder.
[0033] In one embodiment of the present invention, the sulfide solid electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 450° C. to 550° C., and the calcination time is 20 h to 30 h, to obtain a sulfide solid electrolyte.
[0034] The present invention also proposes an all-solid-state lithium-ion battery, comprising a plurality of bipolar pole pieces and a solid electrolyte membrane, wherein a positive electrode active material layer and a negative electrode active material layer are respectively arranged on both sides of the bipolar pole piece, the positive electrode active material layer and the negative electrode active material layer between adjacent bipolar pole pieces are arranged oppositely, and the solid electrolyte membrane is arranged between adjacent bipolar pole pieces. Among them, the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte membrane include the above-mentioned sulfide solid electrolyte to improve the performance of the all-solid-state lithium-ion battery.
[0035] In one embodiment of the present invention, the solid electrolyte membrane is prepared by, for example, a dry method. Specifically, the sulfide solid electrolyte Li a P 1-b M b S c O d X eand a dry binder in a mass ratio of, for example, 99.5:0.5 to 96:4, and then repeatedly ground in a mortar, and then manually rolled repeatedly to form a film, and then repeatedly rolled in a vertical roller press to a preset thickness. Among them, the dry binder is, for example, polytetrafluoroethylene (PTFE) and its derivatives. In one embodiment of the present invention, the preset thickness of the solid electrolyte membrane is, for example, 10μm to 20μm. By compounding the sulfide solid electrolyte with the binder, the processing performance of the sulfide solid electrolyte can be greatly improved, and the mechanical stability of the solid electrolyte membrane can be enhanced.
[0036] In another embodiment of the present invention, the solid electrolyte membrane is prepared by, for example, a wet process, wherein the wet process binder is dissolved in an organic solvent to a preset concentration, and then the sulfide solid electrolyte Li is added according to a mass ratio. a P 1-b M b S c O d X e , mix evenly to obtain a solid electrolyte slurry, the solid electrolyte slurry is, for example, scraped onto a mold by a coating machine, and after the organic solvent is volatilized at room temperature, it is placed in a vacuum oven to dry and demould. Among them, the method binder includes but is not limited to one or more of fluororubber, polyvinylidene fluoride (Polyvinylidene Difluoride, PVDF) and its derivatives or hydrogenated nitrile rubber (HNBR) and its derivatives, etc., the organic solvent is, for example, butyl butyrate, etc., the preset concentration is, for example, 8wt% to 12wt%, the mass ratio of the sulfide solid electrolyte to the wet binder is, for example, 99.5:0.5 to 96:4, and the preset thickness of the solid electrolyte membrane finally obtained is, for example, 10μm to 20μm. In another embodiment of the present invention, a porous high-strength substrate such as a non-woven fabric or polyimide is used as a support, and the solid electrolyte slurry is coated to obtain a solid electrolyte membrane. By controlling the mass ratio of the sulfide solid electrolyte and the binder, the film-forming performance and the conductive performance of the solid electrolyte membrane are taken into account.
[0037] In one embodiment of the present invention, the bipolar pole piece includes a bipolar current collector and a positive electrode active material layer and a negative electrode active material layer respectively arranged on the two side surfaces of the bipolar current collector, wherein the bipolar current collector includes, for example, a positive electrode conductive layer, a bonding conductive layer and a negative electrode conductive layer, and the bonding conductive layer is arranged between the positive electrode conductive layer and the negative electrode conductive layer. In one embodiment of the present invention, the positive electrode conductive layer includes, for example, but is not limited to at least one of aluminum, aluminum alloy, titanium, nickel, magnesium or magnesium, etc., the negative electrode conductive layer includes, for example, but is not limited to at least one of copper, copper alloy, nickel, nickel alloy or stainless steel, etc., and the material of the bonding conductive layer includes, for example, but is not limited to at least one of conductive carbon black, acetylene black, conductive graphite, conductive carbon nanotubes, conductive fibers, aluminum metal or copper metal, etc. The present application does not limit the thickness of the positive electrode conductive layer, the bonding conductive layer and the negative electrode conductive layer, which are specifically selected according to the manufacturing requirements. In a specific embodiment of the present invention, the thickness of the positive electrode conductive layer is, for example, 8μm to 10μm, the thickness of the bonding conductive layer is, for example, 4μm to 9μm, and the thickness of the negative electrode conductive layer is, for example, 8μm to 10μm.
[0038] In one embodiment of the present invention, the positive electrode active material layer is arranged on the positive electrode conductive layer, and the positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder and the above-mentioned sulfide solid electrolyte. The present application does not specifically limit the specific types of positive electrode active materials, conductive agents and binders. Materials known in the art that can be used in lithium ion batteries can be used, and those skilled in the art can choose according to actual needs. In one embodiment of the present application, the positive electrode active material includes but is not limited to lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium-rich manganese-based oxide (LRMO) and lithium-containing phosphates, etc. One or more, lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The binder is, for example, selected from polyvinylidene fluoride or polytetrafluoroethylene. The conductive agent is, for example, selected from one of carbon black, acetylene black, graphene, carbon nanotubes or carbon nanofibers, etc., or a combination of two or more of the above in any proportion. In the positive electrode active material layer, the mass ratio of the positive electrode active material, the conductive agent, the binder and the sulfide solid electrolyte is, for example, (61-88):(1-2):(1-2):(20-25).
[0039] In one embodiment of the present invention, the negative electrode active material layer is arranged on the negative electrode conductive layer, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and the above-mentioned sulfide solid electrolyte. The present application does not specifically limit the specific types of the negative electrode active material, the conductive agent and the binder. The materials known in the art that can be used in lithium-ion batteries can be used, and those skilled in the art can choose according to actual needs. In one embodiment of the present application, the negative electrode active material includes but is not limited to one or more of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compounds or silicon carbon compounds. The conductive agent is, for example, selected from one of carbon black, acetylene black, graphene, carbon nanotubes or carbon nanofibers, or a combination of two or more mixed in any proportion. The binder is selected from any one of polyacrylic acid (PAA), lithium acrylate (PAALi), sodium polyacrylate (PAAS), polyacrylicamide (PAM), polyvinyl alcohol (PVA) or styrene butadiene rubber (SBR) or a combination thereof mixed in any proportion. In the negative electrode active material layer, the mass ratio of the negative electrode active material, the conductive agent, the binder and the sulfide solid electrolyte is, for example, (61-88): (1-2): (1-2): (20-25).
[0040] In one embodiment of the present invention, the positive electrode active material, the conductive agent, the binder and the sulfide solid electrolyte are dispersed in a non-polar solvent according to a mass ratio, and the non-polar solvent is, for example, xylene, etc., to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode conductive layer (i.e., the current collector) of the bipolar current collector, and after drying, cold pressing and other processes, a positive electrode active material layer is formed on the bipolar current collector. The negative electrode active material, the conductive agent, the binder and the sulfide solid electrolyte are dispersed in a non-polar solvent according to a mass ratio, and the non-polar solvent is, for example, xylene, etc., to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode conductive layer of the bipolar current collector formed with the positive electrode active material layer, and after drying, cold pressing and other processes, a bipolar pole piece is obtained. In other embodiments, the present application does not limit the preparation method, process, etc. of the positive electrode active material layer and the negative electrode active material layer, and dry preparation can also be adopted.
[0041] In one embodiment of the present invention, a plurality of bipolar pole pieces are stacked and arranged. In the process of stacking the plurality of bipolar pole pieces in sequence along the stacking direction, the positive electrode active material layer and the negative electrode active material layer of the adjacent bipolar pole pieces are arranged relative to each other, and a solid electrolyte membrane is arranged between the adjacent stacked electrode pieces. The solid electrolyte membrane is arranged between the positive electrode active material layer and the negative electrode active material layer of the adjacent bipolar pole pieces to complete the series connection of the plurality of bipolar pole pieces, and finally form a bipolar battery with, for example, 10 battery cells. Finally, an aluminum-plastic film is packaged on the outside of the bipolar battery to complete the packaging process once and only once, and then formation, capacity division and aging are performed. By using a solid electrolyte membrane in a bipolar battery, the packaging steps can be reduced, the use of packaging materials can be greatly reduced, and the energy density of the bipolar battery can be greatly improved. At the same time, the all-solid-state lithium-ion battery avoids the use of electrolyte and can also improve the safety performance of the lithium-ion battery.
[0042] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0043] Example 1
[0044] The sulfide solid electrolyte Li 5.5 P 0.98 In 0.02 S 3 O 1.5 Cl 1.46 It is mixed with the binder PTFE in a mass ratio of 99:1, repeatedly ground in a mortar, and then manually rolled repeatedly to form a film. It is then repeatedly rolled in a vertical roller press to 15μm to obtain a solid electrolyte membrane.
[0045] The positive electrode conductive layer of the bipolar current collector is aluminum foil with a thickness of 8 μm, the bonding conductive layer is conductive carbon black with a thickness of 5 μm, and the negative electrode conductive layer is copper foil with a thickness of 8 μm. 0.9 Co 0.05 Mn 0.05 O 2 , carbon black, polyvinylidene fluoride and Li 5.5 P 0.98 In 0.02 S 3 O 1.5 Cl 1.46 After mixing in a mass ratio of 75:1:1:23, xylene was added and stirred until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode conductive layer of the bipolar current collector, and after drying, cold pressing and other processes, a positive electrode active material layer was obtained. Silicon carbon compound, carbon black, styrene butadiene rubber and Li 5.5 P 0.98In 0.02 S 3 O 1.5 Cl 1.46 After mixing at a mass ratio of 75:1:1:23, xylene was added and stirred until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode conductive layer of the bipolar current collector, and after drying, cold pressing and other processes, a bipolar pole piece was obtained.
[0046] The bipolar pole pieces and solid electrolyte membranes are assembled, packaged, formed, capacity divided and aged to obtain an all-solid-state lithium-ion battery.
[0047] Example 2
[0048] The solid electrolyte membrane is prepared by wet method. 5.5 P 0.98 In 0.02 S 3 O 1.5 Cl 1.46 The mass ratio of the fluororubber to the binder is 99:1, and other operations are consistent with Example 1.
[0049] Example 3
[0050] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.97 In 0.03 S 3 O 1.5 Cl 1.44 , other operations remain the same as those in Example 1.
[0051] Example 4
[0052] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.99 In 0.01 S 3 O 1.5 Cl 1.48 , other operations remain the same as those in Example 1.
[0053] Example 5
[0054] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Al 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0055] Example 6
[0056] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Ga 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0057] Example 7
[0058] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Sb 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0059] Example 8
[0060] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Bi 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0061] Example 9
[0062] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Sc 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0063] Example 10
[0064] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 Ti 0.02 S 3 O 1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0065] Embodiment 11
[0066] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 As 0.02 S 3 O1.5 Cl 1.46 , other operations remain the same as those in Example 1.
[0067] Example 12
[0068] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.96 As 0.04 S 3 O 1.5 Cl 1.5 , other operations remain the same as those in Example 1.
[0069] Embodiment 13
[0070] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.92 As 0.08 S 3 O 1.5 Cl 1.5 , other operations remain the same as those in Example 1.
[0071] Embodiment 14
[0072] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.96 V 0.04 S 3 O 1.5 Cl 1.5 , other operations remain the same as those in Example 1.
[0073] Embodiment 15
[0074] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.96 Nb 0.04 S 3 O 1.5 Cl 1.5 , other operations remain the same as those in Example 1.
[0075] Example 16
[0076] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 In 0.02 S 3 O 1.5 Br 1.46 , other operations remain the same as those in Example 1.
[0077] Embodiment 17
[0078] The sulfide solid electrolyte in the solid electrolyte membrane and bipolar pole piece is changed to Li 5.5 P 0.98 In 0.02 S 3 O 1.5 I 1.46 , other operations remain the same as those in Example 1.
[0079] Comparative Example 1
[0080] The solid electrolyte membrane is replaced with an electrolyte in which the lithium salt is LiPF 6 The solvent is ethylene carbonate (EC) and diethyl carbonate (DEC), and the mass ratio of EC to DEC in the solvent is 3:7. The electrolyte contains LiPF 6 The concentration was 1 mol / L, and other operations were consistent with Example 1.
[0081] Comparative Example 2
[0082] The mass ratio of EC to DEC in the solvent was 5:5, and other operations were consistent with Comparative Example 1.
[0083] Comparative Example 3
[0084] Diethyl carbonate was replaced by propylene carbonate (PC), and other operations were consistent with Comparative Example 1.
[0085] In Examples 1-17 and Comparative Examples 1-3 of the present invention, different sulfide solid electrolytes and preparation methods are used to obtain lithium-ion batteries. The lithium-ion batteries prepared above are subjected to long-cycle charge and discharge at 25°C, and their discharge capacity is measured, and the energy density is calculated. The working voltage range of the battery test is 2.8V-4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% (80% State of Health, 80% SOH) of the first cycle capacity, the test is terminated to obtain the number of cycles at room temperature.
[0086] Table 1. Performance test results of lithium ion batteries in Examples 1-17 and Comparative Examples 1-3
[0087]
[0088] Referring to Table 1, comparing Examples 1-17 with Comparative Examples 1-3, when using the sulfide solid electrolyte of the present application to fabricate an all-solid bipolar battery, the capacity, cycle life, and energy density of the lithium-ion battery can be improved. Taking the ternary nine-series as the positive electrode active material and the silicon-based negative electrode as an example, with a sulfide solid electrolyte designed to match, the energy density of the lithium-ion battery can be as high as over 450 Wh / kg, and for the all-battery after only one final sealing, it can stably cycle more than 1000 times, reducing the packaging steps and the use of packaging materials, and significantly improving the energy density of the battery. After replacing the solid electrolyte membrane with an electrolyte solution, the lithium-ion battery short-circuits. Therefore, applying the sulfide solid electrolyte to a bipolar battery can simplify the packaging process of the bipolar battery and improve the performance of the bipolar battery.
[0089] Referring to Table 1, comparing Example 1 and Example 2, when the solid electrolyte membrane is fabricated using different processes, such as dry preparation and wet preparation, the performance of the lithium-ion electrode is comparable, indicating that solid electrolyte membranes obtained by different preparation methods can all improve the performance of the lithium-ion battery. Comparing Examples 1, 3, 4 with Examples 11-13, when the content of M in the sulfide solid electrolyte Li a P 1-b M b S c O d X e increases from small to large, the capacity, cycle life, and energy density of the lithium-ion battery first increase and then decrease, indicating that the preferred value range of b is 0 < b < 0.1, and when M is +5 valence, the best value of b is 0.04, and when M is +3 valence, the best value of b is 0.02, so that the battery capacity, cycle life, and energy density of the lithium-ion battery reach the best.
[0090] Referring to Table 1, comparing Example 1 with Examples 5-10 and Example 12 with Examples 14-15, when different +3 valence or +5 valence elements are selected for M in the sulfide solid electrolyte Li a P 1-b M b S c O d X e and the best content is selected for b, the battery capacity, cycle life, and energy density of the lithium-ion battery are all maintained in a relatively high range, indicating that by selecting different M elements, the performance of the lithium-ion battery can be improved. Comparing Example 1 with Examples 16-17, when the sulfide solid electrolyte Li a P 1-b M b S c O d X eWhen different halogen atoms are selected as X, the battery capacity, cycle number and energy density of the lithium-ion battery are maintained in a high range, and when Cl is selected, the performance of the lithium-ion battery is the best.
[0091] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0092] In summary, the present invention proposes a sulfide solid electrolyte and a preparation method and application thereof. By introducing +3 or +5 valence M elements and O elements into the sulfide solid electrolyte, PO and MS bonds are formed in the crystal structure, thereby increasing the intrinsic resistance to atmospheric degradation and effectively reducing H 2 The generation of S increases the possibility of the battery in actual production, thereby enhancing the air stability and chemical stability of the sulfide solid electrolyte. The sulfide solid electrolyte has higher stability and specific reactivity, which can improve the conductivity of the sulfide solid electrolyte, enhance air stability, and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials. Halogen elements are introduced to stabilize the matrix structure of the sulfide solid electrolyte to improve ionic conductivity and electrochemical stability, and improve voltage stability. By using solid electrolyte membranes in bipolar batteries, the packaging steps can be reduced, the packaging process of bipolar batteries can be simplified, the use of packaging materials can be greatly reduced, and the battery capacity, cycle number and energy density of bipolar batteries can be greatly improved, while improving the safety performance of lithium ions.
[0093] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0094] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A sulfide solid electrolyte, characterized in that: The molecular formula of the sulfide solid electrolyte is Li a P 1- b M b S c O d X e ; where: 5 < a < 6; 0 < b < 1; 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb; X is selected from one or more of Cl, Br or I.
2. The sulfide solid electrolyte according to claim 1, characterized in that M is selected from one or more of Sb, In and Bi.
3. The sulfide solid electrolyte according to claim 1, characterized in that X is selected from Cl; the value range of b is 0<b<0.
1.
4. A method for preparing the sulfide solid electrolyte according to any one of claims 1 to 3, characterized in that: Includes steps: According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; and The sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain the sulfide solid electrolyte.
5. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The raw materials include Li2S, LiX, P2S5 and oxides corresponding to the element M, X is selected from one or more of Cl, Br or I, and M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb.
6. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The ball milling time is 20h~30h, the ball milling speed is 500rpm~600rpm, and the ball-to-material ratio is 35:1~45:
1.
7. The method for preparing a sulfide solid electrolyte according to claim 4, characterized in that: The preset temperature is 450° C. to 550° C., and the calcination treatment time is 20 h to 30 h.
8. An all-solid-state lithium-ion battery, characterized in that: At least: A plurality of bipolar pole pieces, each of which has a positive electrode active material layer and a negative electrode active material layer disposed on both sides thereof, and the positive electrode active material layer and the negative electrode active material layer between adjacent bipolar pole pieces are disposed opposite to each other; and A solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between adjacent bipolar pole pieces; Wherein, the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte membrane include the sulfide solid electrolyte according to any one of claims 1 to 3.
9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: In the positive electrode active material layer or the negative electrode active material layer, the content of the sulfide solid electrolyte is 20 wt % to 30 wt %.
10. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The solid electrolyte membrane comprises the sulfide solid electrolyte and a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.
11. An electronic device, characterized in that: An all-solid-state lithium-ion battery comprising any one of claims 8 to 10.